PROBLEM BASED LEARNING IN BASIC PHYSICS - IV - Mody, A.K.; Pradhan, H.C. (SCHOOL SCIENCE, 2014)
In this article- fourth in the series of articles we present problems for a problem based learning course from the area of heat, thermodynamics and optics. We present the learning objectives in this area of basic physics and what each problem tries to achieve with its solution. In this article, fourth in the series of Problem Based Learning in Basic Physics, we present problems on heat, thermodynamics and optics. Methodology and philosophy of selecting these problems are already discussed. (Pradhan 2009, Mody 2011) To review methodology in brief, we note here that this PBL (Problem Based Learning)starts after students have been introduced to formal structure of Physics. Ideally students would attempt only main problem. If they find it difficult, then depending upon their area of difficulty, right auxiliary problem have to be introduced by teacher who is expected to be a constructivist facilitator. Teacher may choose as per her/his requirement or may construct questions on the spot to guide student to right idea and method.